A case report of membrane induction combined with RIA technique for the repair of distal humerus segmentary bone defect - Wang, Guoliang; Zhu, Zhenfeng; Lu, Shuaikun; Wang, Linhu; Gao, Hao; Fu, Congxiao; Ren, Jun; Liu, Xiang; Zhang, Yong; Zhang, Yunfei (Frontiers in Endocrinology, 2023)
Bone nonunion and bone defect are common postoperative complications in clinic. Membrane induction or Ilizarov technique is often used to repair bone defect. Autologous bone is often used for bone defect repair and reconstruction, and the anterior superior iliac spine, posterior superior iliac spine or fibula bone is used as the donor area for bone extraction, but there are problems of donor area complications. In recent years, the development of bone marrow aspiration (RIA) has provided a new alternative way for the source of autogenous bone. We report a 48-year-old female patient with a comminted supracondylar intercondylar fracture of the left humerus due to a car accident. After 8 months of emergency debridement and suture with Kirschner wire internal fixation, the fracture was found to be unhealed with extensive bone defects. We used membrane induction combined with RIA technology to repair and reconstruct the patients, and found good osteogenesis through late follow-up. In theory, membrane induction technique can realize the reconstruction of large segmental bone defects, but the scope of repair is often limited by the lack of autologous bone source. The emergence and development of RIA technology provides us with a new autologous bone donor area for bone repair and reconstruction surgery. It can provide a large amount of high-quality cancellar bone mud through minimally invasive means. Meanwhile, it can reduce patients' pain, infection, fracture, aesthetics and other problems caused by iliac bone extraction, and shorten patients' bed time. Maximize the preservation of the patient's autologous bone source. For the first time in the world, we reported the combination of membrane induction technology and RIA technology in the treatment of segmental bone defects, providing a new idea for the treatment of bone defects.